Logistics performance of European Union markets: Towards the development of entrepreneurship in the transport and storage sector - A. Mesjasz-Lech (Global Journal of Environmental Science and Management)
The markets globalization is one of the factors creating conditions for the development of entrepreneurship. Entrepreneurship does not have one generally accepted definition. Most often, entrepreneurship is perceived as the ability to increase the number of enterprises. Entrepreneurship can be understood as the potential to identify and use development opportunities regardless of own resources. Entrepreneurship is therefore associated with such areas as new organizational forms, stimulation of innovation and cooperation with the entrepreneurial environment. Unfortunately, enterprises face many difficulties which can have the supply and demand nature. These difficulties hinder the enterprise functioning on the market and its development. Logistics performance perceived as the implementation of the highest quality of logistics standards allows overcoming the difficulties of entrepreneurship, especially for the transport and storage sector. For this reason, the article aims to determine the relationship between logistics performance and the entrepreneurship rate for selected European Union countries. Logistics performance was determined by a synthetic measure of development estimated using numerical taxonomy methods for variables forming the Logistics Performance Index. The same method was used to build the entrepreneurship rate, accepting as variables selected entrepreneurship indicators for the transport and storage sector. The correlation analysis was performed with the use of the Spearman rank correlation coefficient. The years 2014-2016 were analyzed. The availability and completeness of data dictated the choice of years, countries and indicators for analysis.